Papua Selatan sebagai Daerah Otonomi Baru dan Kesiapannya Menuju Pemilu 2024 [South Papua as a New Autonomous Regions and Readiness for 2024 Elections] - Pugu, Melyana Ratana; Wambrauw, Meyland Sabrina (Sekretariat Jenderal DPR RI, 2023)
This paper aims to provide an analysis of the readiness of South Papua Province as one of the provinces resulting from the expansion of Papua Province in its readiness for the upcoming 2024 general election. This paper finds that the need for a New Autonomous Region Province, one of which is South Papua Province, is preparing various things towards the success of the upcoming simultaneous general elections in 2024. The important thing needed in welcoming this democratic party is to prepare human resources for election organizers, election participants and also prepare the people of South Papua to get to know well the electoral region and constituency in the upcoming election. In addition, the people of South Papua also need to prepare themselves to participate directly in this general election contestation so that they can bring the aspirations directly of the region. This paper uses exploratory qualitative research methods, namely explaining the data obtained through secondary data, namely through journals, online mass media and government regulations, then the data is triangulated to get the truth. The output of this paper is the importance of the readiness of the South Papua Provincial government as a new autonomous region in preparing human resources and supporting tools for orderly implementation towards a democratic party in 2024. The need for orderly administration of organizers and active socialization to the community as participants in voting rights in elections so that people know their representatives from each constituency and the seats represented can bring the aspirations of the people in the new autonomous region of Papua as well as South Papua Province.AbstrakTulisan ini bertujuan memberikan analisa terkait kesiapan Provinsi Papua Selatan sebagai salah satu Provinsi hasil pemekaran Provinsi Papua dalam kesiapannya menuju pemilihan umum 2024 mendatang. Tulisan ini menemukan bahwa perlunya Provinsi Daerah Otonomi Baru salah satunya adalah Provinsi Papua Selatan mempersiapkan berbagai hal menuju suksesnya pemilihan umum serentak tahun 2024. Hal penting yang diperlukan dalam menyongsong pesta demokrasi ini adalah mempersiapkan sumber daya manusia penyelenggara pemilihan umum, peserta pemilihan umum dan juga mempersiapkan masyarakat Papua Selatan untuk mengenal dengan baik wilayah pemilihan dan daerah pemilihan dalam pemilu mendatang. Selain itu masyarakat Papua Selatan juga perlu menyiapkan diri untuk berpartisipasi secara langsung dalam ajang kontestasi pemilihan umum ini sehingga dapat membawa langsung aspirasi dari wilayahnya. Tulisan ini menggunakan metode penelitian Kualitatif eksploratif yaitu menjelaskan data yang didapatkan melalui data sekunder yaitu melalui jurnal, media massa online maupun peraturan pemerintah kemudian data ditriangulasi sehingga mendapatkan kebenaran. Luaran dari tulisan ini adalah pentingnya kesiapan pemerintah Provinsi Papua Selatan sebagai daerah otonomi baru dalam mempersiapkan sumber daya manusia dan perangkat pendukung untuk tertib penyelenggaraan menuju pesta demokrasi tahun 2024. Perlunya tertib administrasi penyelenggara dan sosialisasi aktif kepada masyarakat sebagai partisipan pemilik hak suara dalam pemilu sehingga masyarakat mengenal wakilnya dari setiap daerah pemilihan dan kursi yang diwakili dapat membawa aspirasi masyarakat di wilayah daerah otonomi baru Papua seperti halnya Provinsi Papua Selatan.